Zadania inwestycyjne jednostek samorządu terytorialnego województwa lubelskiego w zakresie ochrony zdrowia = Investment projects of local government units in the province of Lublin about health care - Martyna Warchoł; Marzea Furtak-Niczyporuk; Małgorzata Pachuta (Kazimierz Wielki University, 2016)
Warchoł Martyna, Furtak-Niczyporuk Marzena, Pachuta Małgorzata. Zadania inwestycyjne jednostek samorządu terytorialnego województwa lubelskiego w zakresie ochrony zdrowia = Investment projects of local government units in the province of Lublin about health care. Journal of Education, Health and Sport. 2016;6(7):336-345. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57960 http://ojs.ukw.edu.pl/index.php/johs/article/view/3695       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Zadania inwestycyjne jednostek samorządu terytorialnego województwa lubelskiego w zakresie ochrony zdrowia   Investment projects of local government units in the province of Lublin about health care   Martyna Warchoł1, Marzena Furtak-Niczyporuk2, Małgorzata Pachuta3   1absolwent Uniwersytetu Medycznego w Lublinie 2Katedra i Zakład Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie,   mgr Martyna Warchoł1 dr n. med. Marzena Furtak - Niczyporuk2 mgr Małgorzata Pachuta3   Adres do korespondencji dr n. med. Marzena Furtak - Niczyporuk Uniwersytet Medyczny w Lublinie 20 - 081 Lublin ul. Chodźki 1       Abstrakt Wprowadzenie Samorząd terytorialny jest to związek publiczno-prawny, powołany przez państwo, ale odrębny od niego. Działa on w obrębie swoich struktur i w zakresie określonym przez nie oraz w ramach obowiązującego prawa. Jednostki samorząd terytorialnego jako podmioty tworzące dla podmiotów leczniczych mają określone w stosunku do tego zadania. Do nich zalicza się, m. in. zadania inwestycyjne. Cel pracy Celem pracy jest przedstawienie zadań inwestycyjnych jednostek samorządu terytorialnego  w zakresie ochrony zdrowia na terenie województwa lubelskiego. Materiał i metody W badaniu zastosowano metodę sondażu diagnostycznego. Narzędziem badawczym był kwestionariusz ankiety własnego autorstwa złożony z 24 pytań. Grupę badaną stanowili urzędnicy 213 samorządów gminnych województwa lubelskiego, z czego 170 to gminy wiejskie, 23 to gminy miejsko - wiejskie, 20 to gminy miejskie. Badania odbywały się na zasadzie anonimowości. Ankiety zostały wysyłane do respondentów za pomocą Internetu. Wyniki i wnioski Z badań wynika, że jednostki samorządu terytorialnego podejmują bardzo okrojone zadania inwestycyjne w zakresie ochrony. Często nie wykonując obowiązkowych zadań do których zobowiązują ich normy prawne.   Słowa kluczowe: jednostki samorządu terytorialnego, ochrona zdrowia, inwestycje.     Abstract Introduction Local government is the relationship of public - legal, appointed by the state, but distinct from it. It works within its structures, and to the extent specified by and under the law. Units of local government units as those that make up for those medicines are determined in relation to this task. These include among others investment tasks. Aim To present investment projects of local government units in the field of healthcare in the Lublin province. Material and Methods The study used diagnostic survey method. The research tool was a questionnaire by their own consisting of 24 questions. The study group comprised 213 officials of local governments Lublin province, of which 170 are rural communes, 23 are of the urban - rural, 20 urban municipalities. Research is carried out on anonymous basis. Surveys were sent to respondents via the Internet. The results and conclusions From the research shows that the local authorities take a very truncated investment projects in the field of protection. Often not performing compulsory tasks which require their legal norms.   Keywords: local government bodies, health care, investment.